Ultramicroporous carbon oxide and preparation method thereof

Through a preparation method including crushing, screening, pre-carbonization, oxidation and low-temperature chemical activation, the problems of high production cost, uneven pore size distribution and low surface reaction activity of ultra-micropore carbon oxide materials are solved, and the preparation of ultra-micropore carbon oxide materials is achieved with the advantages of high surface oxygen content and narrow pore size distribution.

CN119591105APending Publication Date: 2025-03-11XI AN JIAOTONG UNIV

Patent Information

Application Number
CN202411636384.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing ultramicroporous carbon oxide materials have high production costs, uneven pore size distribution and low surface reactive activity.

Method used

Using a preparation method including crushing, screening, pre-carbonization, oxidation and low-temperature chemical activation, ultramicroporous carbon oxide materials with high surface oxygen content and narrow pore size distribution are prepared by controlling the conditions of each step.

Benefits of technology

The low-cost and efficient preparation of ultramicroporous carbon oxide materials has been achieved, with the surface oxygen content reaching 16.94%, the volume contribution rate of pores below 1 nm is as high as 74.64%, and the production cost is significantly reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591105A_ABST
    Figure CN119591105A_ABST
Patent Text Reader

Abstract

The invention provides ultra-microporous carbon oxide and a preparation method thereof, and relates to a preparation method for preparing ultra-microporous carbon oxide with high specific surface area, small aperture, narrow aperture distribution and high surface oxygen content through low-temperature activation. The method comprises the following steps: crushing, screening and cleaning a precursor carbon source to obtain powder with uniform texture; pre-carbonizing the powder, and pickling to obtain a substrate carbon material; carrying out pre-oxidation treatment on the substrate carbon material in air to obtain an oxidized substrate carbon material; and adding an activating agent to activate the substrate carbon material, and pickling to obtain the oxidized ultra-microporous carbon. The surface sample content of the carbon material prepared by the preparation method of the low-temperature regulation oxidized ultra-microporous carbon provided by the invention is up to 16.94%, the contribution rate of pore volume below 1nm is up to 74.64%, and the pore size distribution is narrow. And the method has the advantages of low activator consumption and low activation temperature, greatly reduces the cost barrier, reduces the equipment loss, and is suitable for industrial large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of adsorption materials, and particularly relates to ultra-microporous carbon oxide and a preparation method thereof. Background Art

[0002] Commonly used adsorption materials have the mechanism of action of physical adsorption, chemical adsorption or a combination of the two. The physical-chemical coupled adsorption mechanism has a wider range of applications due to its stronger selectivity. Pure chemical adsorption achieves the adsorption function by bonding through electron transfer or displacement at the molecular or atomic level, and its force is greater than that of physical adsorption. When considering the reuse of materials, it is hoped that the adsorbed material is easy to desorb, that is, the adsorption force should not be too strong. Under this requirement, physical adsorption based on van der Waals force or electrostatic force is more advantageous. Therefore, based on the requirements of adsorption and desorption, the force between the adsorbent material and the adsorbed material can be effectively regulated by physical-chemical coupling.

[0003] Silica gel has abundant mesopores and excellent chemical stability, and can effectively adsorb carbon dioxide and charged ions under various environments. However, its strong hydrophilicity greatly affects the adsorption capacity of other organic molecules under high humidity environments. Zeolite molecular sieves have regular microporous channel structures, which can effectively perform molecular recognition. The hydrophilicity and hydrophobicity of the molecular sieve can be effectively adjusted by regulating the silicon-aluminum ratio of its skeleton. However, its adsorption capacity for large molecules is weak and it is difficult to regenerate after use, which limits its efficiency in practical applications. Metal organic frameworks (MOFs) have ultra-large specific surface area and porosity, special channel structures, and open metal sites, which give them huge adsorption capacity and loading capacity, but the high synthesis cost and poor thermal stability limit their large-scale application. Porous carbon materials have the advantages of abundant pore structures, excellent thermal stability, long service life, and simple regeneration. They show strong adsorption capacity and good adsorption effect, and are currently the most commonly used adsorption materials.

[0004] From the perspective of the preparation methods of porous carbon materials, the methods for constructing their pore structures mainly include: (1) structural genetic method, such as porous carbon obtained by carbonization of MOF, whose pores are inherited from the pore structure of MOF, but its raw material and production costs are too high, making it difficult to carry out large-scale production; (2) template method, that is, the pore structure is obtained by the "occupancy-removal" process of the template material. In this method, the pore structure is closely related to the properties of the template precursor. For hard templates such as silicon dioxide and zinc oxide, their size is much larger than 1 nm, which does not meet the requirements of ultra-micropores. Soft templates such as zinc and ionic liquids need to be heat treated at higher temperatures, which will lose a large number of surface oxygen functional groups and affect surface activity; (3) activation method, that is, the carbon matrix is ​​etched to form pores by reacting with an activator and carbon. It includes physical activation method and chemical activation method. The physical activation method usually uses water vapor and carbon dioxide as activators, and the pore volume and specific surface area of ​​the porous carbon obtained are small, and the adsorption capacity is limited. The commonly used activators in the chemical activation method are potassium hydroxide, zinc chloride, phosphoric acid, etc. The prepared porous carbon has a large specific surface area and rich surface functional groups, but the pore size distribution is wide.

[0005] In summary, a simple, efficient and low-cost preparation technology for ultra-microporous oxidized carbon materials is urgently needed. At present, the main problems in the preparation of ultra-microporous oxidized carbon materials are: (1) the production cost is too high. (2) the content of surface oxygen functional groups is difficult to control, and the loss of oxygen-containing functional groups during the preparation process is large, which affects the surface activity of ultra-microporous carbon. Summary of the invention

[0006] The present invention aims to solve the problems of high production cost, uneven pore size distribution and low surface reactivity of existing ultra-microporous carbon oxide, and to provide a simple, efficient and inexpensive ultra-microporous carbon oxide and a preparation method thereof.

[0007] The present invention is achieved by adopting the following technical solutions: A method for preparing ultra-microporous carbon oxide comprises the following steps: Step 1: The precursor carbon source is crushed, sieved, washed, centrifuged and dried to obtain a precursor carbon source powder with uniform texture; Step 2: pre-carbonizing the dried precursor carbon source powder in an inert atmosphere, acid washing and drying to obtain a base carbon material; Step 3: properly oxidize the base carbon material in air, adjust the surface and shallow layer oxygen content, and obtain an oxidized base carbon material; Step 4: After the activator and the oxidized base carbon material are fully mixed, a chemical activation treatment is performed. This process will form pores and regulate the oxygen content on the pore surface. The resulting product is acid-washed and dried to obtain an ultra-microporous oxidized carbon material.

[0008] A further improvement of the present invention is that in step 1, the precursor carbon source comprises a mixture of one or more of biomass, resin, plastic, carbohydrate and coal-based derivatives; During the screening process, the mesh size of the sieve is 300-800 meshes.

[0009] A further improvement of the present invention is that in step 2, the pre-carbonization treatment is to heat the precursor carbon source at 400-800 ºC for 2 hours at a heating rate of 5-10 ºC / min from room temperature under nitrogen or argon to control the bulk oxygen content in the base carbon material.

[0010] A further improvement of the present invention is that in step 2, the pickling process specifically includes: stirring the pre-carbonized precursor carbon source powder in the pickling solution for 12 hours, then filtering it, and washing it with sufficient deionized water to neutrality to reduce the content of impurities.

[0011] A further improvement of the present invention is that in step three, the appropriate oxidation temperature in the air is between 300 and 400 ºC, and the oxidation time is 2 to 12 hours, the purpose of which is to control the carbonyl content on the surface of the base carbon material.

[0012] A further improvement of the present invention is that in steps 2 and 4, the pickling solution in the pickling process is 1 mol / L hydrochloric acid, nitric acid or 0.5 mol / L sulfuric acid.

[0013] A further improvement of the present invention is that in step 4, the activator is one or both of sodium hydroxide and potassium hydroxide; The mass ratio of the activator to the base carbon material is 1:1 to 5:1.

[0014] A further improvement of the present invention is that in step 4, the sufficient mixing is to first dissolve the activator in deionized water, then add the oxidized base carbon material, stir for 30 minutes, and dry at 80 ºC.

[0015] A further improvement of the present invention is that in step 4, the activation treatment is to heat the uniformly mixed activator and base carbon material at 300-500 ºC for 2 h at a heating rate of 5-10 ºC / min from room temperature under nitrogen or argon.

[0016] Ultra-microporous oxidized carbon is prepared by the preparation method. The surface sample content of the ultra-microporous oxidized carbon is as high as 16.94%, the volume contribution rate of pores below 1 nm is as high as 74.64%, and the pore size distribution is narrow.

[0017] Compared with the prior art, the present invention has at least the following benefits: 1. The raw materials of this preparation method are of various types, widely available, cheap and easy to obtain. Different precursor carbon sources are pre-carbonized to obtain base carbon materials, which reduces the influence of the differences in the physical and chemical properties of different precursors on the preparation of ultra-microporous carbon oxides, gets rid of the dependence on specific raw materials, and greatly improves its added value; Second, the preparation method carries out activation treatment at a relatively low temperature. On the one hand, the prepared ultra-microporous oxidized carbon surface has abundant oxygen functional groups and high reaction activity. On the other hand, it can significantly reduce the damage of the alkaline activator to the equipment, greatly prolong the service life of the equipment, and reduce energy consumption; 3. This preparation method uses a low amount of alkaline activator. The prepared ultra-microporous carbon oxide has a large specific surface area, a narrow pore size distribution, and a high proportion of pores below 1 nm. It has unique structural advantages. In addition, the low amount of activator can greatly reduce the production cost, which is conducive to large-scale industrial production.

[0018] In summary, the surface oxygen content of the ultra-microporous carbon oxide material prepared by the present invention reaches 16.94%, and the volume contribution rate of pores below 1 nm is as high as 74.64%, which meets the needs of greenhouse gas capture, filtration separation, gas sensing, catalysis and other fields. The preparation process not only gets rid of the constraints of raw materials, but also can complete the activation at a lower temperature and a low amount of activator, which is very likely to break the cost barrier of the existing technology and carry out large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 3 are the nitrogen isothermal adsorption-desorption curves of the ultramicroporous carbon oxide prepared in Examples 1, 2 and 3 of the present invention.

[0020] Figure 2 1 is the pore size distribution curve of the ultramicroporous carbon oxide prepared in Examples 1, 2 and 3 of the present invention.

[0021] Figure 3 a is the nitrogen isothermal adsorption-desorption curve of the ultra-microporous carbon oxide prepared in Examples 4, 5 and 6 of the present invention, Figure 3 b is its pore size distribution curve.

[0022] Figure 4 a is the nitrogen isothermal adsorption-desorption curve of the ultra-microporous carbon oxide prepared in Examples 7, 8 and 9 of the present invention, Figure 4 b is its pore size distribution curve.

[0023] Figure 5 a is the pore volume of the ultra-microporous carbon oxide prepared in Examples 1 to 9 with pores less than 1 nm, Figure 5 b is the contribution rate of pore volume below 1 nm.

[0024] Figure 6 a is the XPS full spectrum of the base carbon material described in step 2, Figure 6 b is its C 1s fine spectrum, Figure 6 c is its O 1s fine spectrum.

[0025] Figure 7 a is the XPS full spectrum of the oxidized base carbon material in step 3, wherein, Figure 7 b is its C 1s fine spectrum, Figure 7 c is its O 1s fine spectrum Figure 8 a is the full XPS spectrum of Example 8 of the present invention, Figure 8 b is its C 1s fine spectrum, Figure 8 c is its O 1s fine spectrum.

[0026] Fig. 9 a is the full XPS spectrum of Example 10 of the present invention, Fig. 9 b is its C 1s fine spectrum, Fig. 9 c is its O 1s fine spectrum. Table 1 shows the specific surface area, pore volume, pore volume below 1 nm and contribution rate of pore volume below 1 nm of the oxidized ultramicropores prepared in Examples 1 to 9 of the present invention. DETAILED DESCRIPTION

[0027] In the following, only some exemplary embodiments are briefly described. As those skilled in the art will appreciate, the described embodiments may be modified in various ways without departing from the spirit or scope of the present invention. Therefore, the drawings and descriptions are considered to be exemplary and non-restrictive in nature.

[0028] It should be understood that when used in this specification and the appended claims, the terms "include" and "comprises" indicate the presence of described features, integers, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components and / or combinations thereof.

[0029] It should also be understood that the terms used in the present specification are only for the purpose of describing specific embodiments and are not intended to limit the present invention. As used in the present specification and the appended claims, unless the context clearly indicates otherwise, the singular forms "a", "an" and "the" are intended to include plural forms.

[0030] It should be further understood that the term "and / or" used in the present description and the appended claims refers to any and all possible combinations of one or more of the associated listed items, and includes these combinations.

[0031] Various structural schematic diagrams of the embodiments disclosed in the present invention are shown in the accompanying drawings. These figures are not drawn to scale, and some details are magnified and some details may be omitted for the purpose of clear expression. The shapes of various regions and layers shown in the figures and the relative sizes and positional relationships therebetween are only exemplary, and may deviate in practice due to manufacturing tolerances or technical limitations, and those skilled in the art may additionally design regions / layers with different shapes, sizes, and relative positions according to actual needs.

[0032] The embodiments of the present invention are described in detail below with reference to the accompanying drawings.

[0033] The following takes a biomass material (palm shell) from the raw material range set by the present invention as an example, and combines the drawings in the embodiments of the present invention to clearly and completely describe the technical scheme in the embodiments of the present invention; of course, other raw materials can also be used to prepare ultra-microporous carbon oxides using this technology. Obviously, the described embodiments are part of the embodiments of the present invention. Based on the embodiments disclosed in the present invention, other embodiments obtained by ordinary technicians in this field without making creative work should all fall within the scope of protection of the present invention.

[0034] The present invention adopts a biomass material (palm shell) as an example of a raw material to provide a method for preparing an ultra-microporous oxidized carbon pore structure by low temperature control. The specific steps are as follows: 1. Prepare precursor carbon source powder with uniform particles: crush the palm shell in a grinder, sieve it with an 800-mesh sieve, wash it with deionized water, obtain the precipitate by centrifugation, and dry it in a 60 ºC forced air oven.

[0035] 2. Carry out pre-carbonization treatment to prepare the base carbon material: put the prepared palm shell powder into a tube furnace, introduce nitrogen or argon, and keep it at 400, 600, and 800 ºC for 2 hours at a heating rate of 5 ºC / min. After cooling to room temperature, immerse it in 1 mol / L hydrochloric acid and stir it for 12 hours, then filter it, wash it with deionized water until it is neutral, and finally put it in a 60ºC forced air oven to dry for 12 hours to obtain palm shell carbon.

[0036] 3. Carry out air pre-oxidation treatment to prepare oxidized base carbon material: Put 2 g of palm shell carbon into a muffle furnace and keep it at 300~400 ºC for 4 hours at a heating rate of 5 ºC / min under air conditions to obtain oxidized base carbon material.

[0037] 4. Prepare ultra-microporous oxidized carbon by low-temperature activation treatment: weigh the activator and the oxidized base carbon material according to the mass ratio of 1:1, 3:1, and 5:1, of which the base carbon material is 0.5 g, pour the mixture into a nickel crucible, add 4 ml of deionized water, and after 30 minutes of ultrasound, dry it in an 80 ºC blast oven for 12 hours. Then put it in a tube furnace, pass nitrogen or argon, and keep it at 300, 400, and 500 ºC for 2 hours at a heating rate of 5 ºC / min. After cooling to room temperature, immerse it in 1 mol / L hydrochloric acid and stir it for 12 hours, then filter it, wash it with deionized water until it is neutral, and finally put it in a 60 ºC blast oven to dry for 12 hours to obtain palm shell-based ultra-microporous oxidized carbon material.

[0038] Wherein, the precursor carbon source in step 1 includes a mixture of one or more of biomass, resin, plastic, carbohydrate, coal-based derivatives, etc.

[0039] In steps 2 and 3, the pickling solution in the pickling process is 1 mol / L hydrochloric acid, nitric acid or 0.5 mol / L sulfuric acid.

[0040] In step 3, the activator is one or both of sodium hydroxide and potassium hydroxide.

[0041] In summary, the present invention prepares a low-temperature ultra-microporous oxidized carbon material through a three-step pyrolysis method, which has an extremely high micropore ratio and meets the material requirements in the fields of gas adsorption, carbon capture, catalysis, steam sensing, etc. The raw materials are widely available, and the differences between different precursor carbon sources can be greatly reduced after pre-carbonization treatment. In addition, the preparation process does not include any expensive raw materials, and the operation is simple. The lower activation temperature can greatly reduce the damage of the alkaline activator to the equipment, extend the service life of the equipment, and significantly reduce the cost of its industrial production. It is very promising as a new technology for large-scale production of ultra-microporous carbon materials.

[0042] The following test is used to verify the effect of the invention: Embodiment 1: A low-temperature controlled ultra-microporous oxidized carbon preparation technology according to an embodiment of the present invention specifically includes the following steps: 1. Prepare a precursor carbon source powder with uniform particles: crush 50 g of palm shell particles in a grinder, pass through an 800-mesh sieve, wash off the floating dust with deionized water, centrifuge and dry to obtain palm shell powder. 2. Pre-carbonization to prepare a base carbon material: weigh 5 g of palm shell powder, and the carbonization conditions refer to step 2, the insulation temperature is 600 ºC, and it is marked as palm shell carbon-600 ºC. 3. Pre-oxidation to prepare an oxidized base carbon material: weigh 2 g of palm shell carbon-600 ºC, the pre-oxidation temperature is 300 ºC, the gas atmosphere is air, and the obtained sample is recorded as palm shell carbon-600 ºC-O. 4. Preparation of ultra-microporous carbon by low-temperature activation treatment: The activation temperature is 300 ºC, potassium hydroxide is used as the activator, the mass ratio of potassium hydroxide to palm shell carbon-600 ºC-O (alkali-carbon ratio) is 1:1, and the other conditions refer to step 3. The obtained sample is marked as 300-1:1.

[0043] Embodiment 2: In the embodiment of the present invention, the activation temperature in step 4 is 300°C, the alkali-carbon ratio is 3:1, and the rest is the same as in embodiment 1, and the obtained sample is marked as 300-3:1.

[0044] Embodiment 3: In the embodiment of the present invention, the activation temperature in step 4 is 300°C, the alkali-carbon ratio is 5:1, and the rest is the same as in embodiment 1, and the obtained sample is marked as 300-5:1.

[0045] Figure 1 The nitrogen isothermal adsorption-desorption curves of the ultramicroporous carbon oxide prepared with the activation temperature at 300 ºC and the alkali-carbon ratio increased from 1:1 to 5:1 all show type I isotherms. Figure 2 is the pore size distribution curve. With the increase of the amount of activator, the number of pores below 1 nm gradually increases, but the specific surface area and pore volume are relatively small.

[0046] Embodiment 4: In the embodiment of the present invention, the activation temperature in step 4 is 400°C, the alkali-carbon ratio is 1:1, and the rest is the same as in embodiment 1, and the obtained sample is marked as 400-1:1.

[0047] Embodiment 5: In the embodiment of the present invention, the activation temperature in step 4 is 400°C, the alkali-carbon ratio is 3:1, and the rest is the same as in embodiment 1, and the obtained sample is marked as 400-3:1.

[0048] Embodiment 6: In the embodiment of the present invention, the activation temperature in step 4 is 400°C, the alkali-carbon ratio is 5:1, and the rest is the same as in embodiment 1, and the obtained sample is marked as 400-5:1.

[0049] Figure 3 a is the nitrogen isothermal adsorption-desorption curve of ultra-microporous carbon oxide prepared at an activation temperature of 400 ºC and an increase in the alkali-carbon ratio from 1:1 to 5:1, both of which show type I isotherms. With the increase in the amount of activator, the specific surface area and pore volume of ultra-microporous carbon increase significantly. Figure 3 b is the pore size distribution curve. It can be seen that compared with the ultramicroporous carbon activated at 300 ºC, the number of pores below 1 nm increases significantly after activation at 400 ºC.

[0050] Embodiment 7: In the embodiment of the present invention, the activation temperature in step 4 is 500°C, the alkali-carbon ratio is 1:1, and the rest is the same as in embodiment 1, and the obtained sample is marked as 500-1:1.

[0051] Embodiment 8: In the embodiment of the present invention, the activation temperature in step 4 is 500°C, the alkali-carbon ratio is 3:1, and the rest is the same as in embodiment 1, and the obtained sample is marked as 500-3:1.

[0052] Embodiment 9: In the embodiment of the present invention, the activation temperature in step 4 is 500°C, the alkali-carbon ratio is 5:1, and the rest is the same as in embodiment 1, and the obtained sample is marked as 500-5:1.

[0053] Embodiment 10: In the embodiment of the present invention, steps one and two are the same as those in embodiment 1, and step three for pre-oxidation treatment of the base carbon material is skipped. The activation parameters in step four are the same as those in embodiment 8, and the obtained sample is marked as 500-3:1-no pre-oxidation.

[0054] Figure 4 a is the nitrogen isothermal adsorption-desorption curve of ultra-microporous carbon oxide prepared at an activation temperature of 500 ºC and an increase in the alkali-carbon ratio from 1:1 to 5:1, both of which show type I isotherms. With the increase in the amount of activator, the specific surface area and pore volume of ultra-microporous carbon increase significantly. Figure 4 b is the pore size distribution curve. It can be seen that the ultramicroporous carbon oxide prepared at 500 ºC has a large number of pores below 1 nm. However, when the alkali-carbon ratio is 5:1, the pore size of the carbon material gradually increases, and the effect of the activator shows pore expansion behavior.

[0055] Figure 5 a The volume of pores less than 1 nm in the ultramicroporous carbon oxide prepared in Examples 1 to 9 is counted, and it can be seen that Examples 5, 6, 8, and 9 all have relatively high pore volumes. Figure 5b The contribution rate of the pore volume less than 1 nm in Examples 1 to 9 is analyzed. It can be seen that the contribution rate of Examples 6 and 9 is significantly reduced. This is because excessive activator dosage will expand the pore size based on the original pores less than 1 nm, resulting in larger pore size and wider pore size distribution of ultramicroporous carbon oxide.

[0056] Figure 6 a is the XPS full spectrum of the base carbon material in step 2, and its oxygen content is 6.50%, Figure 6 b and c are the C 1s and O1s fine spectra, from which it can be seen that the oxygen-containing functional groups mainly exist on the carbon surface in the form of C=O.

[0057] Figure 7 a is the XPS full spectrum of the oxidized base carbon material described in step 3, and its oxygen content is 7.15%. Figure 7 b and c are the C1s and O 1s fine spectra, from which it can be seen that the carbonyl content on the surface of the base carbon material increases after pre-oxidation treatment.

[0058] Figure 8 a is the full XPS spectrum of Example 8, and its oxygen content increases to 16.94%. Figure 8 b and c are the C 1s and O 1s fine spectra. It can be seen that the peak intensity of CO increases significantly, which provides higher surface activity for ultramicroporous carbon oxides.

[0059] Fig. 9 a is the full XPS spectrum of Example 10, and its oxygen content is 12.06%. Fig. 9 b and c are the C 1s and O 1s fine spectra. It can be seen that the peak intensity of CO is weak, which proves the necessity of pre-oxidation treatment for the preparation of ultra-microporous carbon oxides.

[0060] Table 1 shows the specific surface area, pore volume, pore volume below 1 nm and contribution rate of pore volume below 1 nm of Examples 1 to 9.

[0061]

[0062] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It is obvious to those skilled in the art that the present invention is not limited to the details of the above exemplary embodiments, and the present invention can be implemented in other specific forms without departing from the spirit or basic features of the present invention. Therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive. The scope of the present invention is defined by the attached claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims are included in the present invention. Any figure mark in the claims should not be regarded as limiting the claims involved.

[0063] In addition, it should be understood that although this specification is described in accordance with the implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment can also be appropriately combined to form other implementation modes that can be understood by those skilled in the art. The above content is only to illustrate the technical idea of ​​the present invention, and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution according to the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A method for preparing ultra-microporous carbon oxide, characterized in that: The following steps are involved: Step 1: The precursor carbon source is crushed, sieved, washed, centrifuged and dried to obtain a precursor carbon source powder with uniform texture; Step 2: pre-carbonizing the dried precursor carbon source powder in an inert atmosphere, acid washing and drying to obtain a base carbon material; Step 3: properly oxidize the base carbon material in air, adjust the surface and shallow surface oxygen content, and obtain an oxidized base carbon material; Step 4: After the activator and the oxidized base carbon material are fully mixed, a chemical activation treatment is performed. This process will form pores and regulate the oxygen content on the pore surface. The resulting product is acid-washed and dried to obtain an ultra-microporous oxidized carbon material.

2. The method for preparing ultra-microporous carbon oxide according to claim 1, characterized in that: In step 1, the precursor carbon source includes a mixture of one or more of biomass, resin, plastic, carbohydrate and coal-based derivatives; During the screening process, the mesh size of the sieve is 300-800 meshes.

3. The method for preparing ultra-microporous carbon oxide according to claim 1, characterized in that: In step 2, the pre-carbonization treatment is to heat the precursor carbon source at 400-800°C for 2 hours at a heating rate of 5-10°C / min from room temperature under nitrogen or argon to control the bulk oxygen content in the base carbon material.

4. The method for preparing ultra-microporous carbon oxide according to claim 1, characterized in that: In step 2, the pickling process specifically includes: stirring the pre-carbonized precursor carbon source powder in the pickling solution for 12 hours, then filtering it, and washing it with sufficient deionized water until it is neutral to reduce the content of impurities.

5. The method for preparing ultra-microporous carbon oxide according to claim 1, characterized in that: In step three, the appropriate oxidation temperature in the air is between 300 and 400 °C, and the oxidation time is 2 to 12 hours, the purpose of which is to control the carbonyl content on the surface of the base carbon material.

6. The method for preparing ultra-microporous carbon oxide according to claim 1, characterized in that: In steps 2 and 4, the pickling solution in the pickling process is 1 mol / L hydrochloric acid, nitric acid or 0.5 mol / L sulfuric acid.

7. The method for preparing ultra-microporous carbon oxide according to claim 1, characterized in that: In step 4, the activator is one or both of sodium hydroxide and potassium hydroxide; The mass ratio of the activator to the base carbon material is 1:1 to 5:

1.

8. The method for preparing ultra-microporous carbon oxide according to claim 1, characterized in that: In step 4, the thorough mixing is to first dissolve the activator in deionized water, then add the oxidized base carbon material, stir for 30 minutes, and dry at 80 ºC.

9. The method for preparing ultra-microporous carbon oxide according to claim 1, characterized in that: In step 4, the activation treatment is to heat the uniformly mixed activator and base carbon material at 300-500 ºC for 2 h at a heating rate of 5-10 ºC / min from room temperature under nitrogen or argon.

10. An ultra-microporous carbon oxide, characterized in that: The ultramicroporous carbon oxide prepared by the preparation method described in any one of claims 1 to 9 has a surface sample content of up to 16.94%, a volume contribution rate of pores below 1 nm of up to 74.64%, and a narrow pore size distribution.

Citation Information

Patent Citations

  • Preparation method of nitrogen-doped porous carbon material for adsorbing CO2

    CN110015662A

  • Method for preparing capacitor material from finely regulated and micro-oxidized carbon material

    CN115966413A

  • Method for producing porous carbon material, porous carbon material and electric double layer capacitor produced by using the material

    JP2001302225A

  • manufacturing method of activated carbon for electric double layer capacitor and the electric double layer capacitor electrode and the capacitor

    KR1020090048779A

  • Method for producing high specific surface area activated carbon using lignocellulosic biomass using resource recycling type advanced activation

    KR102599131B1

Cited By

  • Production process of porous carbonaceous material for solid-state battery

    CN120829160A